How far to investigate presumed psychosomatic symptoms: Lessons from a particular case…. Issue 2 (4th March 2017) - De Scheerder, Marie Angélique; Rottey, Sylvie; Mariman, An; Praet, Marleen; Vogelaers, Dirk
Abstract : We describe a 43-year-old patient with subacute appearance of neurological and atypical complaints of anergia, anorexia and weight loss six months earlier. In spite of several admissions in different hospitals, no underlying somatic cause could be found and he was admitted to a psychiatric hospital with a tentative diagnosis of major depressive disorder. Subsequently, he was referred to the unit of medically unexplained physical symptoms within the department of general internal medicine for assessment by the psychiatrist, involved in this programme. Based on clinical suspicion and red flag symptoms such as involuntary weight loss, a broader internal medicine reassessment, including FDG whole-body PET–CT was requested. Neurological clinical exam showed minor deviations, but neither brain imaging nor a lumbar puncture were contributory. However, FDG PET–CT revealed abnormal moderately to intensely FDG positive lymph nodes in the retroperitoneum. Laparoscopic lymph node biopsy indicated germ cell tumour metastasis. Anti-NMDA antibody positivity allowed a diagnosis of paraneoplastic anti-NMDA encephalitis. Treatment of the underlying disease, a pure seminoma stadium II, consisting of orchidectomy and chemotherapy, resulted in a spectacular regression of 'psychosomatic' symptoms with long-term ability to return to work, and documented disappearance of the anti-NMDA antibody response.